A review of marine water sampling methods for trace metals. Issue 3 (22nd September 2020) - Noble, A. E.; Tuit, C. B.; Maney, J. P.; Wait, A. D.
Abstract: This review summarizes government agency and scientific organization guidance for collecting representative, reliable, and defensible water samples for trace metal analysis, and provides a framework for choosing appropriate sampling techniques to meet a study's data quality objectives, with respect to Natural Resource Damage Assessment in the marine environment. Preventing or limiting contamination is a primary concern during the sampling process, with the goal of constraining sampling-related contamination to below the targeted screening levels. Best practices should include clean-hands/dirty-hands sampling techniques and acid-washed plastic sample bottles. Quality control samples should be collected to detect and quantify contamination and to monitor the precision of the measurement process.